INTERNATIONAL COSTS TO IMPORT AND EXPORT - Rodríguez Chavez, Agustin (2016)
The constantly experienced changes by the international business processes are caused policy changes of the countries, the new technologies or the implementation of corporative business strategies facing logistics operators and fluctuations of economy. For this reason, in the present time it important to study and analyze the costs associated with imports and exports. In 2010, Peru imported 21 billion dollars and exported 13 billion dollars. Then, in 2015 we imported 14 billion dollars and exported 27 billion dollars. This change leads us to propose structures which reflect the costs associated with the processes import and export. Today we must monitor the behavior of costs differentiating them from acquisition costs in accordance with IAS 2 Inventories, evaluating direct and indirect costs of the process as these should be integrated or excluded from the cost of acquisition. The differences in exchange rates of currencies associated with the process, forces us to analyze the impact on cost considering also that according to IAS 21 The Effects of Changes in Exchange Rate of Foreign Exchange, the exchange differences are not part of the acquisition cost, specially, if the total costs are associated with pricing in foreign currency.